Tindak Tutur Direktif dalam Program Televisi Masterchef Indonesia Galeri 8 - Arsyita Rahma Fitzgelard; Hernando Gerrymartino; Muhammad Akhbar Novianto; Shalma Widyawati; Afrizal Adi Prayoga (Haluan Sastra Budaya, 2024)
Through language, humans convey utterances about thoughts, ideas, and feelings. Communication is not just sending language through words but also through behavior or actions. Human actions when uttering utterances are called speech acts. In this study, we will discuss directive speech acts. Directive speech acts are speech acts performed by speakers so that speakers perform the actions mentioned in the utterance. Directive speech acts include those of ordering, inviting, asking, begging, suggesting, advising, and advising. Research related to directive speech acts in the television program Master Chef Indonesia Galeri 8 uses descriptive methods in the form of qualitative research. There are two data analysis methods used in this study. The method of providing the data used in this research is the listening method with the free-engagement speaking technique and the note-taking technique. Directive illocutionary speech acts are divided into five types, namely, commanding, ordering, advising, recommending, and begging. The data found is classified based on the existing speech acts. In the discussion section, the results of the analysis of each piece of data displayed have been presented. In this study, a number of data have been found which have been analyzed and classified based on the form of the utterances made.